Differentiated Learning Models: Students’ Learning Style, Readiness, and Interest in Learning Regarding the Results of Fiqh - Purwowidodo, Agus; Mufidah, Lukluk Nur (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
The differentiation learning model is a novel approach that caters to the demands of the 21st- century education system. Studies conducted by Indonesian scholars on this model are scarce, with limited focus on its impact on students' cognitive abilities and metacognitive awareness. Therefore, this study seeks to investigate the impact of incorporating a differentiated learning approach founded on the learning preferences, preparedness, and engagement of pupils on Fiqh's academic performance. An explanatory survey technique employing the Stratified Random Sampling methodology is utilized in this research. The sample comprises all fifth-grade students of the State Islamic Primary School in Tulungagung Regency, amounting to a total of 507 learners. The study's sample comprises four randomly selected State Islamic Primary Schools from the seven Tulungagung Regency, with a total of 276 students studying Fiqh. The data collection instruments used include test sheets for learning outcomes, notes on creative thinking skills, and motivation questionnaires. The data is then analyzed using a two-way Analysis of Variance (ANOVA) with a significance level of 5%. The results of the research indicate that: (1) There is no discernible disparity in Fiqh learning outcomes based on learning style. (2) There is no disparity in Fiqh learning outcomes based on students’ learning readiness. (3) Disparities in Fiqh learning outcomes based on students’ learning interests exist. (4) A noteworthy interaction exists between the implementation of differentiation learning aspects of learning styles, learning readiness, and students’ learning interests on Fiqh learning outcomes. The findings of this study suggest that the differentiation learning model provides an alternative approach to learning that addresses the needs of the modern era.